(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
South Africa has delivered several voices of standing on the country’s colonial historiography. The impact of especially 19th and 20th century colonialism on the southern tip of Africa is deeply rooted in all spheres of life, and its visibility mostly surfaced in former apartheid South Africa. In this paper, the historiography of colonialism in South Africa is concisely introduced with, as a second key aim, the discussion of a way in which FET history learners and HET history students could practically understand and experience South Africa’s colonial past by exploring a regional/local colonial or post-colonial legacy. By using colonialism as topic, it is also argued that it is possible to teach any history content (whether from the FETCAPS History curriculum content or from the variety of HET history module content) more efficiently if the topic, phenomenon or concept is studied in the light of regional/local examples.